Omega-3 polyunsaturated fatty acids in atrial fibrillation prevention after coronary bypass surgery - B. A. Tatarsky (Кардиоваскулярная терапия и профилактика)
Aim. To assess omega-3-polyunsaturated fatty acids (w-3-PUFA) effects on atrial arrhythmogenicity in patients with coronary heart disease, who underwent coronary bypass surgery (CBS). Material and methods. In total, 50 patients, who underwent CBS, were examined. All participants were divided into two groups. Group I included 25 patients with atrial fibrillation (AF) episodes in anamnesis, who were administered w-3-PUFA (2 g/d) one week before and 7 days after CBS. Group II, control group, included 25 patients without AF in anamnesis, who did not receive w-3-PUFA. Atrial conduction abnormalities were registered by non-invasive, high-definition transesophageal electrocardiography. Results. In Group II, 7 AF cases (28%) were registered during early post-CBS period. AF paroxysm incidence was maximal in the first two days after CBS. In Group I, AF paroxysms were registered in 4 patients (16%), on Day 2-3 after CBS. Clinical symptoms were less severe in Group I than in Group II: in the former, two patients had asymptomatic AF episodes. No AF cases required cardioversion, terminating spontaneously. Group I patients demonstrated increased right and left atrium conductivity. Conclusion. In patients with post4CBS AF risk, w-3-PUFA therapy was associated with arrhythmia risk reduction, pontaneously terminating AF episodes, and less severe hemodynamic disturbances. Adding w-3-PUFA to standard therapy is effective and safe in CBS patients.